Constructing Religious Legitimacy in the Digital Public Sphere: A Study of Islamic Discourse on Social Media - Muhammad Riyyan Firdaus; Mohamad Dindin Hamam Sidik (UIN Sunan Gunung Djati Bandung, 2024)
Purpose: This study aims to analyse how Akmal Sjafril constructs religious authority through narrative framing, linguistic strategies, and value integration in his social media engagement. Methodology: This research employed a qualitative approach using virtual ethnography (netnography) to examine Akmal Sjafril’s digital narratives on Twitter. Data were collected through virtual observation, documentation of tweets, and semi-structured interviews, and were analysed using an interactive model of qualitative analysis. Findings: The study reveals that Akmal Sjafril systematically builds religious authority by constructing narratives that defend Islamic teachings against liberal and secular reinterpretations, using adaptive linguistic styles to engage a diverse digital audience, and embedding core Islamic values—such as interfaith tolerance, noble character, and critical thinking rooted in faith—into his digital communication. His approach demonstrates how religious figures can sustain both credibility and audience engagement in a fragmented digital public sphere, blending theological consistency with communicative adaptability. Research Implications: These findings contribute to the broader understanding of religious authority in the digital era by showing how figures can negotiate credibility through adaptive digital strategies without compromising doctrinal authenticity. The research suggests the need for digital literacy initiatives, ethical guidelines for religious communication, and institutional support for promoting comprehensive religious narratives in online spaces. Originality/Value: This study provides a unique contribution by integrating narrative construction, linguistic adaptation, and value-based communication into the analysis of digital religious authority, offering new insights into how Islamic figures navigate legitimacy within the networked dynamics of social media environments.